First evidence of crayfish plague agent in populations of the marbled crayfish (Procambarus fallax forma virginalis) - Keller N.S.; Pfeiffer M.; Roessink I.; Schulz R.; Schrimpf A. (Knowledge and Management of Aquatic Ecosystems, 2014)
The introduction of non-indigenous species and associated diseases can cause declines in indigenous flora and fauna and threaten local biodiversity. The crayfish plague pathogen (Aphanomyces astaci), carried and transmitted by latent infected North American crayfish, can lead to high mortalities in indigenous European crayfish populations. Although the parthenogenetic marbled crayfish (Procambarus fallax (Hagen, 1870)  forma virginalis) is common in the aquarium trade and has established wild populations in Europe, its carrier status is still unknown. This study investigated one captive and three established wild-living marbled crayfish populations for an infection with the crayfish plague pathogen applying real-time PCR. We demonstrate that captive, as well as two wild marbled crayfish populations were infected by A. astaci. Although infection status in laboratory kept specimens reached high levels, marbled crayfish showed no obviously plague-related mortality. Furthermore, sequence analysis revealed that captive crayfish carried the A. astaci genotype Pc, which has earlier been isolated from the North American red swamp crayfish (Procambarus clarkii). The results indicate that due to its positive carrier status marbled crayfish poses a greater threat to local biodiversity in Europe than considered until now.